Drawing Religious Information Experiences Across Time: Timelines as a Graphic Elicitation Method - Guzik, Elysia (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2016)
Visual, arts-based methods are widespread in other social sciences but remain marginal in information science. Applying “timelining” (Sheridan, Chamberlain, and Dupuis, 2011) in information research can expand our understanding of connections among information, time, affect and inexpressible religious experiences, while fostering collaboration between researchers and participants and across disciplines. Les méthodes s’appuyant sur les arts visuels sont très répandues dans les autres sciences sociales, mais elles demeurent marginales dans les sciences de l'information. L'utilisation de la mise en séquence chronologique (Sheridan, Chamberlain, et Dupuis, 2011) dans les sciences de l'information est susceptible d’élargir notre compréhension des liens entre l’information, le temps, les affects et certaines expériences religieuses inexprimables, tout en favorisant la collaboration entre les chercheurs et les participants dans toutes les disciplines.